Ileostomy closure in a patient with severe pulmonary hypertension and COPD - Anaesthetic consideration - Garg, Ankur; Engineer, Smita R.; Patel, Kiran (International Journal of Scientific Reports, 2016)
High morbidity and mortality occur in patients with pulmonary hypertension (PH) undergoing non-cardiac surgery under any type of anaesthesia technique. Right heart failure occurs due to increased pressure in pulmonary artery secondary to pain, stress and ventilation. It is important to maintain preload, ventricular contractility, pulmonary vascular resistance and right ventricular afterload. It is also necessary to avoid hypoxia, hypercarbia, hypothermia and pain. A 45 year old male patient, known case of chronic obstructive pulmonary disease (COPD) with severe PH was posted for ileostomy closure. General anaesthesia (GA) with epidural catheter for analgesia was given.